Operations Management For Dummies - Anderson, Mary Ann (Wiley, 2013)
Score your highest in Operations Management Operations management is an important skill for current and aspiring business leaders to develop and master. It deals with the design and management of products, processes, services, and supply chains. Operations management is a growing field and a required course for most undergraduate business majors and MBA candidates. Now, Operations Management For Dummies serves as an extremely resourceful aid for this difficult subject. Tracks to a typical course in operations management or operations strategy, and covers topics such as ev.
Chapter 16: Responding to Risks That Threaten Your Project. - Print version record
Keywords: Production management; Business logistics; Project management; Production; Gestion; Logistique (Organisation); Gestion de projet; BUSINESS & ECONOMICS; Production & Operations Management; Productiemanagement; Bedrijfsprocessen; Productieplanning